2022
DOI: 10.3390/life13010097
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Symptoms 15 Months since COVID-19 Diagnosis: Prevalence, Risk Factors and Residual Work Ability

Abstract: Background: A proportion of patients’ ailments may last after recovering from acute COVID-19, with episodic and systemic symptoms of unclear etiology potentially involving different organs. Study aim: The aim of this study was to investigate the persistence of symptoms 15 months since COVID-19 diagnosis in patients referring to the post-COVID-19 clinic in Trieste (north-eastern Italy). Methods: Two-hundred-forty-seven patients were medically examined between 8 December 2020–6 April 2021, after a median time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 51 publications
(79 reference statements)
7
24
0
Order By: Relevance
“…Our study revealed that female sex was the only independent predictor of fatigue in a cohort of previously hospitalised patients, both in the acute phase of COVID-19 and also four and 12 weeks since the onset of infection. Our results accord with a recent Italian study of 247 patients that also confirmed the prognostic role of female sex in the persistence of neurological and psychiatric symptoms, including fatigue, seven weeks after the initial SARS-CoV-2 infection [31]. However, researchers also pointed to older age and the presence of comorbidities, especially depression, as additional risk factors for residual post-COVID symptoms, but that cohort comprised individuals approximately one decade younger than ours, with only less than half of them requiring hospitalisation due to COVID-19 [31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study revealed that female sex was the only independent predictor of fatigue in a cohort of previously hospitalised patients, both in the acute phase of COVID-19 and also four and 12 weeks since the onset of infection. Our results accord with a recent Italian study of 247 patients that also confirmed the prognostic role of female sex in the persistence of neurological and psychiatric symptoms, including fatigue, seven weeks after the initial SARS-CoV-2 infection [31]. However, researchers also pointed to older age and the presence of comorbidities, especially depression, as additional risk factors for residual post-COVID symptoms, but that cohort comprised individuals approximately one decade younger than ours, with only less than half of them requiring hospitalisation due to COVID-19 [31].…”
Section: Discussionsupporting
confidence: 92%
“…Our results accord with a recent Italian study of 247 patients that also confirmed the prognostic role of female sex in the persistence of neurological and psychiatric symptoms, including fatigue, seven weeks after the initial SARS-CoV-2 infection [31]. However, researchers also pointed to older age and the presence of comorbidities, especially depression, as additional risk factors for residual post-COVID symptoms, but that cohort comprised individuals approximately one decade younger than ours, with only less than half of them requiring hospitalisation due to COVID-19 [31]. Another recent study revealed that among 400 Brazilian patients previously hospitalised due to COVID-19, female sex, hypercholesterolemia, obesity and prone position in the acute phase of disease increased the risk of post-COVID syndrome, with fatigue prevalent in 42% and 27% of cases within three and six months after discharge, respectively [32].…”
Section: Discussionsupporting
confidence: 92%
“…An important factor that determines sustainable return to work is the perceived work ability, which is also more independent of the specific context than return to work and occupational changes. To date, few studies have evaluated work ability in the context of PCC within specific populations of health-care workers and patients attending a post COVID-19 clinic (17,22). Evidence from this study and other studies demonstrated lower work ability scores among those with PCC, with a higher reduction among those with occupational changes.…”
Section: Main Findings In Contextmentioning
confidence: 55%
“…Evidence on the impact of PCC on the occupational situation and work-related impairments due to PCC is limited and heterogenous (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Prior studies have reported that between 11% and 50% of individuals do not return to work (2,14,26) and that 10% to 72% do not fully regain their work capacity 6 to 12 months after infection (7,23,26,27).…”
Section: Main Findings In Contextmentioning
confidence: 99%
See 1 more Smart Citation